Uji Aktivitas Antibakteri dan Antioksidan dari Metabolit Ekstraseluler Bakteri Endofit Tumbuhan Mahang (Macaranga bancana): Antibacterial and Antioxidant Activity Test of Extracellular Metabolites of Endophytic Bacteria of Mahang Plants (Macaranga bancana) - Chang, Helen; Pujiyanto, Sri; Prastya, Muhammad Eka; Primahana, Gian; Yuswan, Apriza; Retnowati, Dwi; Permatasari, Vera (Departemen Biologi, Institut Pertanian Bogor, 2024)
The increasing pollution which promotes accumulation of free radicals and a significant number of bacterial resistances to antibiotics have prompted various efforts to search for new sources of bioactive compounds. The aim of this study was to investigate the antibacterial and antioxidant properties of bioactive compounds produced by endophyte bacteria from M. bancana. The most potential bacterial isolate was extracted its active constituents until obatined crude extract and tested using disc diffusion technique and detemined MIC and MBC values. Antioxidant properties using DPPH radicals were performed followed by GC-MS analysis of its crude extract. We obtained that MB3.1 isolate exhibited antibacterial activity against all four tested bacteria including Escherichia coli strain ATCC 8739, Pseudomonas aeruginosa strain ATCC 9027, Staphylococcus aureus strain ATCC 25923, and Bacillus subtilis strain ATCC 6633. The best MIC values of this extract were shown against B. subtilis with an MIC value of 39.06 μg/ml. Further, MB3.1 extract showed a moderate antioxidant activity with an IC50 value of 248.19 μg/ml. GC-MS analysis of MB3.1 extract revealed 10 dominant compounds, including phenylethyl alcohol, benzeneethanol, 4-hydroxy, and tryptophol, which might be responsible for the antibacterial and antioxidant properties.